(untitled) - Iovine, John (New York, 2002)
This title is unique in its coverage of a wide variety of robot types: walker robots, solar-ball robots, acrobots, underwater bots, and robotic hands. No prior technical skills are required. Following an introduction to robotics and AI, the text discusses the various components of robot construction: power systems, drive systems, sensors, intelligence, speed controllers, and even neural networks
Keywords: Robotics,Trung tâm Học liệu ĐHCT; Amateurs’ manuals,Kỹ thuật robot